Febrile neutropenia management and outcomes in hematopoietic cell transplantation for chronic granulomatous disease. Issue 2 (10th March 2022) - Parta, Mark; Cuellar‐Rodriguez, Jennifer; Gea‐Banacloche, Juan; Qin, Jing; Kelly, Corin; Zerbe, Christa S.; Holland, Steven M.; Malech, Harry L.; Kang, Elizabeth M.
Abstract: Objective: We analyzed events and therapies related to febrile neutropenia in patients receiving hematopoietic cell transplantation (HCT) for chronic granulomatous disease (CGD). Methods: Three protocols for HCT were used to extract the relation between conditioning and infectious complications during transplantation for CGD, especially the relation of fever and neutropenia to microbiological events and antibiotic therapy. Results: Sixty‐nine recipients received either reduced intensity conditioning with matched related or unrelated donors or conditioning specific to haploidentical‐related donors utilizing posttransplant cyclophosphamide. Fever prior to neutropenia was common (52) and in eight recipients, Gram negative bacterial infection occurred prior to neutropenia, and in nine during neutropenia. Alemtuzumab as conditioning was associated with preneutropenic infection. Empiric therapy (noncarbapenem) by institutional guideline was given in 40. Carbapenems were given before neutropenia (8) or as empiric therapy in neutropenia (18), or a switch to a carbapenem ( n = 22) occurred in 48 cases. No deaths related to infection associated with neutropenia occurred. Conclusion: The management of febrile neutropenia in HCT for CGD led to no deaths related to infection associated with neutropenia. Bacteremias occurred both prior to neutropenia and during neutropenia. Bacteria isolated may have represented the recrudescence of prior infection, representing the population transplanted and the platform for HCT. The treatment of prior infections may have had an influence on the necessity of carbapenem use as either empiric or directed therapy for bacterial infections.